Optimization of district heating systems for future uncertain conditions: Deterministic and stochastic linear modelling - Malmgren, Fanny; Skoglund, Henrik (My University, 2021)
In Sweden, the demand for space heating and hot water is mainly supplied by district heating. Factors with high uncertainty, such as electricity price, heat demand, policies and climate strategies, affects the future development of district heating. The risks associated with these uncertainties must be managed while capitalizing on opportunities of improvements and optimization of the district heating system. This thesis investigates to what extent uncertainty analysis is important for district heating system planning. To this end, this thesis investigates the sensitivity of operational patterns and investment choices of Swedish district heating systems to uncertainty in biofuel costs, electricity price, availability of industrial waste heat and the heat demand of the system. This is done by the development of two brownfield district heating system optimization models, a deterministic and a stochastic one in the modeling language GAMS. The models are linear and optimize investments and dispatch of three district heating type systems with respect to minimizing the annualized total system cost. The conclusion is that technologies with low investment cost, mainly electric boilers, are favored when uncertainties are considered. In general, power-to-heat technologies are favorable to give the district heating systems the ability to adapt to the electricity and biofuel prices and to be cost-efficient in many future outcomes. The electricity production from combined heat and power units varies depending on the electricity price, at high electricity price combined heat and power units maximize their electricity production and at low electricity prices they refrain from up to 50% of the electricity production, in favor of producing additional heat. Furthermore, the sizing of thermal energy storage is sensitive to the uncertain parameters, resulting in different storage capacities depending on how the uncertainties affect the marginal value of heat. The value of accounting for uncertainties varies between the systems, and the system with a greater mix of technologies is less sensitive to the uncertainties applied. A risk has been identified that potential economic benefits can be missed out on if uncertainties are not considered, either by not meeting the demand due to lack of capacity or by not being able to capitalize on low electricity prices.